Evaluation of the Level of Health Awareness of the Players of the Iraqi Premier League in Handball - Ahmed Kadhim Abdulkareem (Journal of Global Pharma Technology, 2018)
The objective of researchSetting levels of the health awareness measure and its application to the players of the Iraqi Premier League handball applicants.Recognition of the level of health awareness of the players of the Iraqi Premier League handball applicants.Evaluation of the level of health awareness of the players of the Iraqi Premier League handball applicants.The researchers used the descriptive method in the survey method to determine the level of health awareness. The scale was applied in the final form to a sample of the players of the Iraqi Premier League in handball for the 2017-2018 sports season. The researchers then set levels for the health awareness measure and applied it to the players of the Iraqi league Hand, and used the researchers Statistical Bulletin of Social Sciences (SPSS) version XVII. The following conclusions were reached:Five levels of health awareness measure have been developed.The ability of the health awareness scale to be applied by the researchers in measuring health awareness.The majority of the players of the Iraqi Premier League handball a poor level in the health awareness measure.Keywords: Health awareness, Premier League and handball.